Prospects and Applications of Biomass-Based Transparent Wood: An Architectural Glass Perspective - Wang, Jing; Zhu, Jian’gang (Frontiers in Chemistry, 2021)
This paper briefly discussed the research progress of biomass-based transparent wood (BBTW), and summarized the key technologies and potential application prospects of BBTW in replacing architectural glass. Based on the introduction of the preparation process of BBTW, the advantages of BBTW and their feasibility to replace architectural glass are illustrated with a view to the requirements and conditions of architectural glass for different use functions. The limitations of BBTW are discussed and the development prospects of BBTW are also prospected. The research shows that BBTW has the advantages of green and renewable materials that can meet the requirements of good lighting conditions, flame retardant, heat insulation and safety, which are in line with the sustainable development trend. Further studies are needed to continuously break through its limitations with an aim to expand the application of this new biomass-based material.